2011
DOI: 10.1083/jcb.201107053
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial-focused genetic interaction map reveals a scaffold-like complex required for inner membrane organization in mitochondria

Abstract: Statement MITO-MAP, a high-density genetic interaction map in budding yeast, identifies a mitochondrial inner membrane–associated complex that promotes normal mitochondrial membrane organization and morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
550
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(621 citation statements)
references
References 79 publications
47
550
0
14
Order By: Relevance
“…Om45 forms a complex with the outer membrane proteins porin and Om14. It has been reported that Om45 is involved in the interaction between outer and inner membrane protein complexes [18,19], thus linking the porin pore to transport proteins of the inner membrane. Studies conducted so far did not lead to the identification of proteinaceous factors required for the import of the Om45 precursor into mitochondria [7,8,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Om45 forms a complex with the outer membrane proteins porin and Om14. It has been reported that Om45 is involved in the interaction between outer and inner membrane protein complexes [18,19], thus linking the porin pore to transport proteins of the inner membrane. Studies conducted so far did not lead to the identification of proteinaceous factors required for the import of the Om45 precursor into mitochondria [7,8,13,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups identified a large protein complex, MICOS complex (mitochondrial contact site and cristae organizing system; previously named MINOS, MitOS, Mitofilin or Fcj1 complex ), that has a crucial role in the formation of cristae junctions, contact sites to the outer membrane, and the organization of inner membrane. [10][11][12][13][14] In yeast, MICOS consists of at least six subunits: Mic60 (Fcj1), Mic10 (Mio10/Mcs10/Mos1), Mic19 (Aim13/Mcs19), Mic26 (Mio27/Mcs29/Mos2), Mic12 (Aim5/ Msc12) and Mic27 (Aim37/Mcs27). In mammals, five subunits of MICOS have already been identified, including Mic60 (Mitofilin/IMMT), Mic10 (MINOS1), Mic19 (CHCHD3/MINOS3), Mic25 (CHCHD6/CHCM1) and Mic27 (APOOL).…”
mentioning
confidence: 99%
“…In human cells, mitofilin was found to interact with the sorting and assembly machinery of the outer membrane (SAM complex) that has a central role in the biogenesis of outer membrane proteins ( Figure 2B) (Xie et al , 2007 ;Darshi et al , 2011 ;Alkhaja et al , 2012 ;Ott et al , 2012 ). In yeast, interactions of mitofilincontaining protein complexes of the inner membrane with the SAM complex, the TOM complex, porin channels and Ugo1 have been reported (Figure 2A) (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;K ö rner et al, 2012 ;Zerbes et al , 2012 ). The interaction of mitofilin with the TOM complex was shown to support the import of precursor proteins into the intermembrane space via the mitochondrial intermembrane space assembly (MIA) machinery (von der Malsburg et al , 2011 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
“…Several recent studies have reported on the discovery of a multi-subunit protein complex of the mitochondrial inner membrane in S. cerevisiae that contains mitofilin as a central component (Harner et al , 2011 ;Hoppins et al , 2011 ;von der Malsburg et al , 2011 ;Alkhaja et al , 2012 ). This protein complex was named the mitochondrial inner membrane organizing system (MINOS) or, alternatively, mitochondrial organizing structure (MitOS) or mitochondrial contact site (MICOS) complex (for an overview of the nomenclature see Herrmann , 2011 ).…”
Section: Mitochondrial Inner Membrane Organizing System (Minos)mentioning
confidence: 99%
See 1 more Smart Citation